Architecture’s Direct Impact - Holly Jacobson; Alan Ricks; MASS Design Group (Oz, 2013)
How valuable is architecture? The effects of the 2008 recession, namely sustained unemployment in the profession still lingering around 13.9%, have forced soul-searching within the discipline. Recent headlines in the New York Times: “Want a Job? Go to College, and Don’t Major in Architecture” lay bare the value proposition of the profession—the public doesn’t see one.